2000
DOI: 10.1007/s004150070152
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of second lumbrical and interosseus latencies with standard measures of median nerve function across the carpal tunnel: a prospective study of 450 hands

Abstract: The second lumbrical-interosseus distal motor latency (2LI-DML) was compared prospectively in 450 hands. Median nerve function was assessed by standard motor and sensory electrophysiological tests. In a control group of 100 hands the upper limit of normal for the 2LI-DML was 0.5 ms. In all hands studied the correlation coefficients of 2LI-DML were higher with sensory nerve tests than with motor studies. Carpal tunnel syndrome (CTS) was diagnosed clinically in 276 hands, and 174 showed no clinical signs of CTS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 16 publications
3
38
0
2
Order By: Relevance
“…3,16 It is a fast, easy-to-perform, median-ulnar motor comparative test that has been widely evaluated against other motor and sensory techniques in the diagnosis of CTS and consistently found to be highly sensitive and specific. 7,9,12 An additional advantage of 2-LINT is its persistence in concomitant polyneuropathy and severe CTS. 3,10 Recently, it has been shown that the premotor potential observed when recording standard 2-LINT represents a near-field median sensory nerve action potential (SNAP) generated by the digital sensory fibers as they cross the recording electrode.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,16 It is a fast, easy-to-perform, median-ulnar motor comparative test that has been widely evaluated against other motor and sensory techniques in the diagnosis of CTS and consistently found to be highly sensitive and specific. 7,9,12 An additional advantage of 2-LINT is its persistence in concomitant polyneuropathy and severe CTS. 3,10 Recently, it has been shown that the premotor potential observed when recording standard 2-LINT represents a near-field median sensory nerve action potential (SNAP) generated by the digital sensory fibers as they cross the recording electrode.…”
mentioning
confidence: 99%
“…9 Because of this, 2-LINT is now commonly employed as a standard test of CTS. 3,16 It is a fast, easy-to-perform, median-ulnar motor comparative test that has been widely evaluated against other motor and sensory techniques in the diagnosis of CTS and consistently found to be highly sensitive and specific.…”
mentioning
confidence: 99%
“…Dies gelingt dann h ä ufi g mittels motorischer Neurografi e. Ä hnlich hohe Sensitivit ä t und Spezifi t ä t wie bei den oben genannten Methoden ergeben sich aber nur dann, wenn auch hier vom Prinzip des intraindividuellen Vergleichs Gebrauch gemacht wird. Besondere Vorteile bietet die von L ö -scher et al [15] genauer untersuchte Methode, mit der in den letzten Jahren breitere Erfahrungen gesammelt wurden. Dazu werden die Ableitelektroden im zweiten Interdigitalraum und ü ber dem Grundgelenk des zweiten Fingers angebracht ( ᭹ ᭤ Abb.…”
Section: Neurografi E Bei Fokalen L ä Sionenunclassified
“…They vary in sensitivity and specificity. In spite of that, the sensory tests are more sensitive and changes in it occur earlier, motor tests are usually recordable in advanced degree of CTS and in patients with peripheral polyneuropathy [2,8]. There are three motor tests that assess the median nerve across the wrist.…”
Section: Introductionmentioning
confidence: 97%